2019
DOI: 10.2147/dddt.s220510
|View full text |Cite
|
Sign up to set email alerts
|

<p>Isolation, pharmacological evaluation and molecular docking studies of bioactive compounds from Grewia optiva</p>

Abstract: BackgroundTraditionally, Grewia optiva is widely used for the treatment of many diseases like dysentery, fever, typhoid, diarrhea, eczema, smallpox, malaria and cough.MethodsShade-dried roots of G. optiva were extracted with methanol. Based on HPLC results, chloroform and ethyl acetate fractions were subjected to silica column isolation and four compounds: glutaric acid (V), 3,5 dihydroxy phenyl acrylic acid (VI), (2,5 dihydroxy phenyl) 3',6',8'-trihydroxyl-4H chromen-4'-one (VII) and hexanedioic acid (VIII) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 20 publications
0
23
0
Order By: Relevance
“…Computational docking experiments were subjected to mimic the characteristics of constituent-target, which is a effective method to screen the active compounds and predict the mechanism of action of compounds. 32 The crystal structure of the key target proteins were obtained from the Protein Data Bank, their information was listed in Table S1. The docking exercise was conducted using Autodock ( Figures S4-S11).…”
Section: Molecular Docking Analysismentioning
confidence: 99%
“…Computational docking experiments were subjected to mimic the characteristics of constituent-target, which is a effective method to screen the active compounds and predict the mechanism of action of compounds. 32 The crystal structure of the key target proteins were obtained from the Protein Data Bank, their information was listed in Table S1. The docking exercise was conducted using Autodock ( Figures S4-S11).…”
Section: Molecular Docking Analysismentioning
confidence: 99%
“…Hiba et al have reported the isolation of octanoic acid, tridecanoic acid, octadecatrienoic acid, and eicosanoic acid from Grewia tenax [ 6 ]. Additionally, previously, we evaluated the Grewia optiva extracts for different biological potentials and isolated eight compounds from this plant [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Acetylcholine (ACh) and butyrylcholine (BCh) are important neurotransmitters in the procurement and storage of transmitted memory and are involved in the transmission of impulses across the synapse. Their levels are reduced in AD [ 7 , 8 , 9 ]. To restore and control the activities of ACh and BCh at the synapse, inhibitors of their respective cholinesterases, acetylcholinesterase (AChE), and butyrylcholinesterase (BChE) are used [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The root of Ziziphus oxyphylla , a medicinal Rhamnaceae plant, exhibited different DPPH and ABTS scavenging potentials when isolated using different type of solvents (Khan et al., 2020). Four bioactive compounds were successfully extracted from roots of Grewia optiva using methanol and fractionated into different solvents, showed antioxidant potentials (DPPH and ABTS) and anticholinesterase activity (inhibits neurodegenerative) (Ul Bari, Zahoor, Zeb, Khan, et al., 2019; Ul Bari, Zahoor, Zeb, Sahibzada, et al., 2019). These studies signified that the antioxidative activity in plant extracts are highly correlated with the amount of the isolated bioactive compounds such as phenolics and flavonoids using different solvent extraction systems.…”
Section: Introductionmentioning
confidence: 99%